Essay on the Geography of Plants - Smith, Ian C. (Ethnobiology Letters, 2013)
Review of Essay on the Geography of Plants. Alexander von Humboldt and Aimé Bonpland. Edited and with an Introduction by Stephen T. Jackson. Translated by Sylvie Romanowski. 2009. University of Chicago Press, Chicago. Pp. 296, 1 color plate, 9 halftones, 7 tables, 1 poster. 45.00 (cloth). ISBN 9780226360669.